EXTRAVERSION AND OPENNESS TO EXPERIENCE AS PREDICTORS OF IMPULSE BUYING BEHAVIOUR AMONG UNDERGRADUATES OF NNAMDI AZIKIWE UNIVERSITY, AWKA - Ezeanya, Ifenna D.; Uzoma, Onyeka Jennifer; Obidigbo, Godwin Chekwubechukwu; Mabia, Chidozie (African Journal of Social and Behavioural Sciences, 2024)
The study examined extraversion and openness to experience as predictors of impulse buying behaviour. The participants in this study were 217 undergraduates of Nnamdi Azikiwe University, Awka. They comprised of 87 male students (40.1%) and 130 female students (59.9%). The age range was 17 to 33 years, with a mean age of 21.62 and a standard deviation of 2.16. Two instruments were used for the study which included: Big Five Personality Inventory (BFPI) (Goldberg, 1993) and Impulse Buying Behaviour Scale (IBBS) (Rook & Fisher, 1955). Cross sectional survey was used for the study while multiple regression was used for data analysis. Two hypotheses were tested and results showed that extraversion significantly and positively predict impulse buying behaviour (β =.14, t = 2.03, p <.05) while openness to experience did not significantly predict impulse buying behaviour among undergraduate students (β = .06, t = .92, p > .05). This implies that individuals with high extroversion personality trait are more likely to engage in impulse buying than those with low extroversion personality trait. It was recommended that students with high extroversion trait can use self-reflection and self-control techniques to manage their impulsive buying tendencies. Additionally, further research on the relationship between personality traits and impulse buying behaviour will help expose how other personality traits not covered by this study affects impulse purchasing.